Baicalin administration could rescue high glucose-induced craniofacial skeleton malformation by regulating neural crest development - Lu, Jia-Qi; Luo, Zhi-Yan; Sun, Chengyang; Wang, Si-Miao; Sun, Dixiang; Huang, Ruo-Jing; Yang, Xuesong; Ding, Yong; Wang, Guang (Frontiers in Pharmacology, 2024)
Hyperglycemia in pregnancy can increase the risk of congenital disorders, but little is known about craniofacial skeleton malformation and its corresponding medication. Our study first used meta-analysis to review the previous findings. Second, baicalin, an antioxidant, was chosen to counteract high glucose-induced craniofacial skeleton malformation. Its effectiveness was then tested by exposing chicken embryos to a combination of high glucose (HG, 50 mM) and 6 μM baicalin. Third, whole-mount immunofluorescence staining and in situ hybridization revealed that baicalin administration could reverse HG-inhibited neural crest cells (NCC) delamination and migration through upregulating the expression of Pax7 and Foxd3, and mitigate the disordered epithelial-mesenchymal transition (EMT) process by regulating corresponding adhesion molecules and transcription factors (i.e. E-cadherin, Ncadherin, Cadherin 6B, Slug and Msx1). Finally, through bioinformatic analysis and cellular thermal shift assay, we identified the AKR1B1 gene as a potential target. In summary, these findings suggest that baicalin could be used as a therapeutic agent for high glucose-induced craniofacial skeleton malformation.